Determination of vitamin losses and degradation kinetics during composting - Ipek, U; Arslan, EI; Öbek, E; Karatas, F; Erulas, FA (Elsevier Sci Ltd, 2005)
The vitamin levels of organic manure such as compost applied to soil are important for plants and soil ecology. For this reason, a knowledge of the variations at the vitamin levels of the material during the recycling of the wastes is necessary to protect or to increase the vitamin content of the materials after biological processing. Vitamin losses during the recycling process and how much vitamin the final products contain are not usually determined. For this purpose, various wastes were composted and vitamin variations during composting determined. Vitamins A and E concentrations of the final product decrease and Vitamin C concentration increases according to the raw vitamin concentrations of the materials. The final product contained Vitamins A, E and C at concentrations of 0.91, 0.31 and 13.15 mug/g, respectively. The degradation of Vitamins A and E during composting could be expressed as first-order kinetics. The reaction rate constants of the degradation of Vitamins A and E were determined as k = 0.0466 and 0.068 per day, respectively. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: composting; degradation; kinetics; vitamin A; vitamin C; vitamin E